Resistansi Identitas Budaya Jakarta dalam Novel Terjemahan yang Berjudul Twilight in DJakarta - Gofur, Gofur; Sajarwa, Sajarwa (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This research is a translation study that examines the process of cultural transfer. It focuses on translation works that preserve the cultural identity of the source text within the target text. To address this issue, the study draws on theories from Baker and Newmark regarding translation strategies and equivalence, Ahimsa-Putra’s cultural categorization, and Venuti’s concepts of resistance in translation. The primary material for this research is the English novel “Twilight in Djakarta,” which is translated from the source text “Senja di Jakarta.” These primary sources yield data in the form of words and phrases that reflect Jakarta's cultural translation and terminology through documentation. To achieve accurate results, the study employs identity and descriptive-qualitative methods to illustrate the translator’s strategies for conveying the source language culture while maintaining its cultural content. The findings reveal that resistance to cultural terms manifests through loanwords, mixed strategies, and word-for-word translations. This approach not only preserves but also enriches the cultural meanings in the target text. Additionally, this research aims to contribute to the preservation and promotion of Indonesian culture in a global context by retaining cultural terms during translation. Ultimately, it suggests that readers of the target text can gain a deeper understanding and appreciation of the cultural context of the source text.